Overview of the Implementation of the Chronic Disease Management Program at Oebobo Community Health Center, Kupang City - Maria Alfonsa Pera; Tasalina Yohana Parameswari Gustam; Rina Waty Sirait; Pius Weraman (Media Kesehatan Masyarakat, 2026)
Hypertension and diabetes mellitus are non-communicable diseases that are the main cause of death in the world, including in the work area of the Oebobo Health Center, Kupang City. The high number of cases of these two diseases encourages the implementation of the Chronic Disease Management Program (prolanis) as a strategic effort to improve the quality of life of sufferers. This study aims to describe the implementation of prolanis in the Oebobo Health Center based on a system approach that includes input, process, and output elements. This study uses a qualitative approach with a case study design. The informants consisted of health workers managing prolanis and program participants with hypertension and diabetes mellitus. Data collection techniques include in-depth interviews, observations, and thematically analyzed documentation. The results of the study show that the implementation of prolanis is supported by sufficient and competent human resources, adequate educational facilities and methods, and assessed educational materials. Core activities include medical consultations, group education, prolanis gymnastics, and home visits. The output of this program includes controllable diseases thus reducing the risk of pain and improving health status. However, obstacles were found such as the limitation of health workers if there were enough participants, irregular attendance, and lack of facilities to support physical activities such as education rooms and gymnastics. In conclusion, the implementation of prolanis at the Oebobo Health Center went quite well and had a positive impact on the participants, although there are still challenges that need to be overcome immediately to achieve optimal results.